2014
DOI: 10.1002/app.40462
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of maleated glycidyl 3‐pentadecenyl phenyl ether as a functionalized plasticizer for styrene–butadiene rubber/carbon black/silica composites

Abstract: Maleated glycidyl 3-pentadecenyl phenyl ether (M-GPPE) was synthesized from glycidyl 3-pentadecenyl phenyl ether (GPPE), a renewable derivative from cardanol, with maleic anhydride (MAH) by grafting copolymerization. The resulting M-GPPE was used as a functionalized plasticizer for a styrene-butadiene rubber (SBR)/carbon black (CB)/silica composite. The effects of M-GPPE on the development of the filler network, the extent of silica dispersion, the curing characteristics, and the mechanical performance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…compounds and SBR/F51 compounds As shown in Figure 7 and Table 2, the T 90 of SBR/ F51 compounds is increased significantly with the increasing loading of F51, indicating that F51 delays the vulcanization, which is ascribed to the consumption of rubber additives by epoxy group of F51 [27]. The T 90 of SBR and SBR/50lignin is 11.18 and 39.54 min respectively, indicating that incorporation of lignin in rubber matrix delays the vulcanization of rubber matrix, which is ascribed to the adsorption between lignin and vulcanization additives [14].…”
Section: Curing Analysis Of Sbr/50lignin/f51mentioning
confidence: 95%
“…compounds and SBR/F51 compounds As shown in Figure 7 and Table 2, the T 90 of SBR/ F51 compounds is increased significantly with the increasing loading of F51, indicating that F51 delays the vulcanization, which is ascribed to the consumption of rubber additives by epoxy group of F51 [27]. The T 90 of SBR and SBR/50lignin is 11.18 and 39.54 min respectively, indicating that incorporation of lignin in rubber matrix delays the vulcanization of rubber matrix, which is ascribed to the adsorption between lignin and vulcanization additives [14].…”
Section: Curing Analysis Of Sbr/50lignin/f51mentioning
confidence: 95%
“…Our previous research results had confirmed that short nylon fibers waste maintained their length upon mixing and had reinforcing effects on Ethylene Propylene Diene Monomer rubber [25]. Moreover, in our lab we had successfully employed Glycidyl 3-Pentadecenyl Phenyl Ether (GPPE), a renewable derivative from cashew nut industry, as a compatibilizer to improve the interface adhesion between SBR and nanoparticle fillers [26,27]. The presence of the epoxy propyl ether group and C 15 unsaturated side chain in GPPE molecule, as shown in Figure 1, facilitates chemical reactions of GPPE with many chemical compounds [28].…”
Section: Introductionmentioning
confidence: 90%
“…Usually, the mechanical property of a plasticized rubber is drastically destroyed. [23][24][25][26] Keeping this fact into consideration, the results are analyzed. Flex fatigue property of composites is mainly considered.…”
Section: Flex Fatigue Property Of Compoundsmentioning
confidence: 99%
“…However, because of the diffusion of the low-molecularweight oily plasticizers in the rubber matrix, these oil-plasticized rubber compounds are subjected to the oozing of oil to the rubber surface and the evaporation of oil at elevated temperatures, leading to the decrease of the mechanical properties over time, especially for stiffness and ex fatigue property. [23][24][25][26] What is worse, they oen migrate or volatilize from polymer matrix due to the low-molecular-weight leading to serious environmental pollutions. 25 Then much attention has been focused on the research of polymeric plasticizers in recent years.…”
Section: Introductionmentioning
confidence: 99%